New perspective in teaching Arabic language: a usage of key word method - Yaakub, Muhamadul Bakir (Universiti Sains Islam Malaysia (USIM), 2016)

(untitled)
Teaching Arabic as a second language is not an easy process. To ensure the success, an Arabic teacher requires specific teaching methods that are dynamic, strategic and effective according to the learning objectives. This study aims to highlight the potential of practicing teaching Arabic as a second language by using ‘keyword’ method in non-Arabs environment. In addition, it is also an attempt to prove the effectiveness in teaching Arabic at a school in Malaysia, explaining its usage in class, in a simple and gradual manner. Thus, it helps the readers who have basic knowledge of the Arabic language, as well as teachers and students who put their effort in learning Arabic. In short, this study can benefit many people, among those are the Arabic language teachers and those who experienced from poor performance in learning the Arabic language. The most important is the relations of this method to the acquisition of Arabic vocabulary, in remembering words that have been learned and applying it within the necessary occasion.